Merger Arbitrage : a Fundamental Approach to Event-Driven Investing - Melka, Lionel; Shabi, Amit. (New York : Wiley, 2012)
A wave of corporate mergers, acquisitions, restructuring, and similar transactions has created unprecedented opportunities for those versed in contemporary risk arbitrage techniques. At the same time, the nature of the merger wave has lent such transactions a much higher degree of predictability than ever before, making risk arbitrage more attractive to investors. Surprisingly, there is little transparency and instruction for investors interested in learning the latest risk arbitrage techniques. Merger Arbitrage - A Fundamental Approach to Event-Driven Investing helps readers underst.
5.1.4 Syndicated loan5.1.5 Mezzanine loans; 5.1.6 The bond market; 5.1.7 Contingent value rights (CVRs); 5.2 The Legal Security of the Financing; 5.2.1 The UK legal framework; 5.2.2 The US legal framework; 5.2.3 The European legal framework in general; Case Study: The Dow Chemical/Rohm & Haas Deal; 6 Competition Risk; 6.1 Origins and Regulatory Framework of Competition Law; 6.1.1 United States; 6.1.2 Europe; 6.2 Competent Authorities and Approval Process; 6.2.1 United States; 6.2.2 Europe; 6.2.3 China; 6.3 Competition Remedies; 6.4 Country Differences in Evaluation.
6.5 The Allocation of Competition Risk between the Parties.
Print version record.
Keywords: Arbitrage; Consolidation and merger of corporations; Stock exchanges and current events; Business; Arbitrage; Consolidation and merger of corporations; Stock exchanges and current events; Electronic books